Uruguay - Shields, Charles J. (Mason Crest Publishers, 2004)
Presents information on the geography, history, economy, and people of Uruguay. Includes a chronology, recipes, project ideas, and more.
Includes bibliographical references and index.
The land -- The history -- The economy -- The people -- The communities.
Presents information on the geography, history, economy, and people of Uruguay. Includes a chronology, recipes, project ideas, and more.
Keywords: Uruguay.; Uruguay / Juvenile literature.